Fabrication of Photodetector and Study of Its Structural and Optical Properties of Cadmium Oxide Thin Films Prepared by Vacuum Thermal Evaporation Method - Maki, Samir A.; AbdulRidha, Zainab S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The fabricated Photodetector n-CdO /-Si factory thin films Altboukaraharara spatial silicon multi- crystallization of the type (n-Type) the deposition of a thin film of cadmium and at room temperature (300K) and thickness (300 Â± 20nm) and the time of deposition (1.25sec) was antioxidant thin films cadmium (Cd) record temperature (673k) for one hour to the presence of air and calculated energy gap optical transitions electronic direct ( allowed ) a function of the absorption coefficient and permeability and reflectivity by recording the spectrum absorbance and permeability of the membrane record within the wavelengths (300 1100nm). was used several the bias ranged between 1-5 Volts. The results showed that this reagent works to the extent spectral 400-1000 nm current revealed these findings also said that factor ideal growing thin films CdO which gives a clear indication of the increased concentration of defects.It Showed the results of measuring volume - an effort that the detector of the type of acute if the value of effort internal construction less CdO of thin films . The studies of the response spectrum showed that these reagents responsiveness characterized Bakmtin : the first at the wavelength of 600 nm and the second at the wavelength 800 nm. The highest value for the responsiveness 0.46 A / W at 800 nm wavelength and using siding